Application of Cinnamaldehyde-Chitosan Coating to Prolong Shelf-Life of Grapefruit (Citrus Maxima) - N. P. Minh (Journal of Global Pharma Technology, 2016)
Grapefruit (Citrus Maxima) is one of the most important citrus fruit cultivated in Vietnam. Its stability is quite short under ambient temperature. The edible coating could keep textural properties, sensory appearance and control respiration rate of fruits by functioning as a semipermeable vapor and gas barrier to regulate the moisture and gases in the package. Chitosan is recognized as safe and has been widely applied as a successful carrier for incorporating with the antimicrobial agents. The objective of this research was to prolong the fresh fruit quality of grapefruit by using cinnamaldehyde-chitosan coating. The results indicated that 1.0% cinnamaldehyde-chitosan application could maintain the highest fruit quality properties such as weight loss, decay rate, firmness, sugar, acidity, and vitamin C. By this application, the storage life of grapefruit could be extended to 28 days under ambient temperature.Keywords: Grapefruit, cinnamaldehyde, chitosan, coating, storage.